Epidemiology of Maternal Periodontal Disease and Preterm Birth among Patient Attending in some Selected Hospital in Dhaka City - Nashida Ahmed, Munnawar Ul Haque, Arsalan Humayun, Tahmina Soomro, Manthar Ali Mallah, Reema Aslam (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Periodontal disease can be a source of subclinical and persistent infection that may induce systemic inflammatory responses that increase the risk of preterm birth. The goal of this study was to establish whether periodontal disease is a risk factor for preterm birth and to evaluate the association of this risk with gestational age. Study Design: This descriptive cross-sectional study included postpartum women with periodontal disease admitted to the maternity care unit of five different medical college hospitals in Dhaka City. Methods: The sample size was 111 postpartum; all of them had mild, moderate, or severe periodontitis. A periodontal examination was performed within 48 hours of delivery to determine the severity of periodontal disease. The outcome variable is preterm birth (define as birth occurring before 37 weeks of gestational age.). The statistical analysis of the data was carried out by using software program SPSS version 17. Results: The prevalence of severe periodontitis was 11.7% (13/111), moderate periodontitis was 36% (40/111), and mild periodontitis was 52.3% (58/111). From the variables that described the socio-demographic characteristics, only age had a significant association with preterm birth, and the mother having a lower age than normal and the mother having higher age than normal had an increased prevalence of preterm birth. From the variables that described the oral health related characteristics, regular visits to a dentist and pain in the tooth had a significant association with preterm birth (P<0.05). From the variables which that described the pregnancy related characteristics, BMI, previous history of miscarriage or abortion, previous history of preterm birth, antenatal check-up, and genital infection had a significant association with preterm birth (P<0.05). From the variables that described the socio-demographic characteristics, only education level had significant associations with periodontitis (P<0.05). Practical implication: The study suggests that periodontal disease may increase the risk of preterm birth in pregnant women. Therefore, improving the periodontal health of pregnant women may improve pregnancy outcomes. Regular visits to the dentist and early treatment of tooth pain may help in identifying and managing periodontal disease in pregnant women. Additionally, healthcare providers should consider periodontal health as a potential risk factor for adverse pregnancy outcomes and incorporate it into prenatal care. However, more research is needed to determine the causal relationship between periodontal disease and preterm birth, and to identify key confounders. Conclusions: Our results suggest that a specific drive to improve the periodontal health of pregnant women could be a means of improving pregnancy outcomes. Nevertheless, it is not clear whether only periodontal diseases play a causal role in adverse pregnancy outcomes. Additional longitudinal, epidemiologic, and interventional studies with clear and consistent definitions of periodontal disease and adverse pregnancy outcomes, sufficiently large sample sizes, and controls for key confounders are needed to validate this association and to determine whether it is causal. Keywords: maternal periodontal disease; preterm birth; risk factors; gestational age; epidemiology; dental visits